Baseline Circulating Activated TFH and Tissue-Like Exhausted B Cells Negatively Correlate With Meningococcal C Conjugate Vaccine Induced Antibodies in HIV-Infected Individuals - Milagres, Lucimar; Silva, Giselle; Pereira-Manfro, Wânia; Frota, Ana Cristina; Hofer, Cristina; Ferreira, Bianca; Barreto, Daniela; Figueredo, Marcelo; Coelho, Barbara; Villela, Lucia; Petrovas, Constantinos; Koup, Richard (Frontiers in Immunology, 2018)
Since 2006, meningococcal serogroup C (MenC) conjugate (MCC) vaccines have been supplied by the Brazilian government for HIV-infected children under 13 years old. For measuring protection against MenC, the serum bactericidal antibody (SBA) assay is the method of choice. The characterization of T follicular helper cells (TFH) cells has been an area of intensive study because of their significance in multiple human diseases and in vaccinology. The objective of this study was to characterize the phenotype of peripheral TFH (peripheral TFH) cells and B cells and how they associated with each other and with SBA levels induced by vaccination as well as with serum cytokine levels of HIV-infected and non-infected children and adolescents. We found that CD27-IgD-CD21-CD38+ (exhausted B cells) as well as short-lived plasmablasts (CD27+IgD-CD21-CD38+) are increased in cART treated HIV patients and negatively associated with MCC vaccine induced SBA levels. Baseline frequency of activated peripheral TFH cells was a negative correlate for SBA response to MCC vaccine but positively correlated with circulating plasmablast frequency. Baseline IL4-levels positively associated with SBA response but showed a negative correlation with activated peripheral TFH cells frequency. The increased frequency of activated peripheral TFH cells found in non-responders to the vaccine implies that higher activation/differentiation of CD4 T cells within the lymph node is not necessarily associated with induction of vaccine responses.